(3VeGf GdYjhH GdNajI ai GdeHjY (B- (3NjGQ GdYjH (B: s (3OQGSI ebGQfI Hjf Gdabg GdESdGei h GdbGfhf GdeOfi (B/ s - (3GdNWGH eMehO Ldhds; (3eMehO HdGd egQGf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3NUUfG gPG GdHMK dOQGSI (B"(3VeGf GdYjhH GdNajI ai GdeHjY(B" (3OQGSI ebGQfi Hjf Gdabg GdESdGei h GdbGfhf GdeOfi GdeUQi h GddjHi(B. (3aJMOKfG Yf eGgjI VeGf GdYjH MjK JWQbfG Edi JYQja GdYjH(B: (3h TQhW KHhJg(B: (3h GdYbhO GdJi jTedgG(B: (3Ke GfJbdfG ddMOjK Yf CMcGe VeGf GdYjH(B. (3h GdPi JVef GdHjhY GdJi jSbW ajgG Mb GdVeGf(B. (3h GdJYOjd GdGJaGbi ddYjH h TQW GdHQGAI efg(B. (3h CNjQG BKGQ OYhi GdVeGf h Mbhb GdeTJQi ajgG(B. (3h YbH Pdc GSJNdUfG YOI CehQ(B: (3CgegG Cf GdTQjYI GdESdGejI (B- (3cYGOJgG (B- (3cGfJ SHGbI ai JfXje CMcGe GdYjH JfXjeG ObjbGs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfj, (B2014s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B256-273s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3GdeHjYs; (3NjGQ GdYjHs; (3VeGf GdYjhH GdNajIs; (3NjGQ GdQDjIs; (3NjGQ GdJYjjfs; (3GTJQGW GdHQGAI ef GdYjHs; (3JTOjO GdVeGfs; (3GdHVGYI GdeHGYI dG JQO hdG JSJHOds; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs